Proceedings of the 1st International Conference on Numerical Modelling in Engineering. NME 2018, 28-29 August 2018, Ghent University, Belgium /: NME 2018, 28-29 August 2018, Ghent University, Belgium. Numerical and modelling in mechanical and materials engineering : Volume 2, ([2019]) - Unknown
No abstract available